Coagulation and Fibrinolytic Mechanisms During and After Normal Childbirth. Issue 5703 (25th April 1970) - Bonnar, John; McNicol, G. P.; Douglas, A. S.
Abstract : A detailed sequential study of the coagulation and fibrinolytic systems in 15 healthy women during normal childbirth showed that striking changes in keeping with activation of the clotting mechanism take place during and after placental separation. Shortening of the clotting-test results, a sharp increase of factors VIII and V, and a decrease of the plasma fibrinogen were found as the placenta separated. Within one hour of normal delivery the levels of fibrin/fibrinogen degradation products increased and fibrinolytic activity returned to normal non-pregnant levels. In the early puerperium a secondary increase took place in the plasma fibrinogen level, factor VIII remained raised, and the platelet count showed a pronounced rise; these changes may explain the increased predisposition to thromboembolic complications in the puerperium.